Revisión de aplicaciones del análisis wavelet en parámetros magnéticos de sedimentos del Holoceno, sur de Argentina - Cappellotto, Luiggina (2024)
The use of mathematical and statistical analysis tools in variables measured in geological records by geophysical methods and related to various natural processes, is important to analyze periodicities at different scales and assess relationships between different forcing agents. Thus, the analysis of the variations of the geomagnetic field (GF) is of particular interest in providing knowledge about its behavior. In this review, we summarize case studies in which these analyses were applied to directional parameters of the GF and magnetic properties of sediments in time series spanning the Holocene. The periodicities found reflect forcings that could be interacting with the GF. Such is the case of periodicities related to a fundamental solar mode and climatic variations in the GF directional parameter record. This fact suggests, on the one hand, that the GF could be a climatic forcing and, on the other hand, that the same external forcing to the planet affects the GF and the climate. Another case study presented shows how magnetic properties, measured in sedimentary sequences sampled at high resolution, were useful for the indirect determination of environmental changes, as well as of the energetic fluctuations of the transport agents involved, in this case, the wind.